2017
DOI: 10.7567/apex.10.062301
|View full text |Cite
|
Sign up to set email alerts
|

High-current perovskite solar cells fabricated with optically enhanced transparent conductive oxides

Abstract: We focused on fluorine tin oxide (FTO)-coated glass substrates for perovskite solar cells (PVSCs) and studied the effects of the optical properties and surface morphology on the short-circuit current density (Jsc). The PVSC on our FTO substrate demonstrated a gain in Jsc by 1.4–1.6 mA/cm2, compared with the PVSCs on commercial FTO substrates. This is attributed not only to the low absorption of the FTO substrate but also to the suppression of reflection loss, caused by the light trapping effect on the textured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Meanwhile, it is also optically useful to introduce such textured structures, which are widely used as a light management technology for several kinds of solar cells to realize a significant improvement in J sc by reducing the reflection loss and increasing the optical path length using light scattering effects, and a similar technology is reported for perovskite single junction solar cells. 22) To satisfy both the uniform coating of perovskite absorber and the light confinement effects of the textured structures, we investigated the impact of gentle textured structures by optical simulations. 23) As shown in Fig.…”
Section: Light Management Technology In Tscsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, it is also optically useful to introduce such textured structures, which are widely used as a light management technology for several kinds of solar cells to realize a significant improvement in J sc by reducing the reflection loss and increasing the optical path length using light scattering effects, and a similar technology is reported for perovskite single junction solar cells. 22) To satisfy both the uniform coating of perovskite absorber and the light confinement effects of the textured structures, we investigated the impact of gentle textured structures by optical simulations. 23) As shown in Fig.…”
Section: Light Management Technology In Tscsmentioning
confidence: 99%
“…We have so far developed device design technology for PSTSCs with two-terminal (2T) structure 15,16) together with three-terminal (3T) 17) and four-terminal (4T) structure by utilizing the knowledge that we have obtained through technological development of thin-film Si solar cells, 18,19) SHJ solar cells, 20,21) and PSC. 22) We developed a top cell technology optimized for the bottom cell which was produced by industrial technology and recently reported a 2T PSTSC, which has bottom cell based on the industrial SHJ technology, with a PCE of 28.8%. 23) In this paper, we review light management technology in TSCs which is indispensable to realize high-efficiency PSTSCs and report our latest results on 2T PSTSCs obtained by improving the PSC of the top cell through an optimization of the device fabrication technology and using the industrial SHJ solar cell technology.…”
Section: Introductionmentioning
confidence: 99%
“…35) Some simulation results indicate the potential realization of a perovskite=c-Si tandem solar cell with a conversion efficiency of over 30%. 36,37) Besides the R&D activities in the fabrication of thin-film and crystalline Si solar cells, we have also developed perovskite solar cells 38) and examined their multijunction structures. 39) To optimize realistic structures of perovskite= c-Si monolithic tandem solar cells, we performed optical simulation based on models combining both wave and ray optics using the measured optical properties of each layer in the high-efficiency c-Si solar cell and perovskite solar cell.…”
Section: Perovskite/c-si Tandem Solar Cellmentioning
confidence: 99%
“…© 2022 The Japan Society of Applied Physics Supplementary material for this article is available online P erovskite solar cells have been gathering an attractive interest from scientific and industrial aspects because high power conversion efficiency (PCE) is achieved by a simple solution process with potential advantages of low-cost manufacturing. [1][2][3][4] Toward commercialization, it is necessary to develop low-cost and reliable coating technology of functional layers uniformly on substrates with rough surface morphology, [4][5][6][7][8][9][10][11] and further challenges should be required. At this point, self-assembled monolayers (SAMs) containing carbazole core are promising as hole transport layers because it is expected to enable conformal coating along the surface morphology by solution process due to the formation of the chemical bond with indium tin oxide (ITO) underlayers.…”
mentioning
confidence: 99%